150 KeV Cu− ion- implantation in SrVO3 thin films: A study of Cu induced defect states. (November 2020) - Saraswat, Himani; Chaudhary, Surekha; Varshney, Mayora; Devi, Devarani; Singh, Fouran; Won, S.O.; Shin, Hyun-Joon; Sharma, Aditya
Abstract: Investigations on the extrinsic defects induced alteration in B–O6 octahedra, energy band-structure amendments and physical assets of ABO3 perovskites are technologically important and require modest approaches for the defect creation and their investigations. In this study, Cu defects have been assimilated in SrVO3 films using 150 KeV Cu ion-implantation with two different ion fluences; 1.63 × 10 15 ion/cm 2 and 8.15 × 10 15 ion/cm 2 . The implanted Cu ions do not make metallic/oxide clusters in SrVO3 films, as confirmed by XRD studies, but have facilitated the lattice parameter enlargement and energy band-gap narrowing by creating their defect states and V–O6 octahedra distortion. NEXAFS spectra at Cu L-edge have confirmed the Cu 2+ ions in low/high Cu doses implanted SrVO3 films. Cu defects induced V–O6 octahedra distortion has manifested a diverse ligand field interaction between V 3 d and O 2p orbitals and has narrowed the; (i) energy gap of V 2p3/2 and V 2p1/2 transitions and (ii) energy gap between t2g /eg and the O 2p and metal (n+1)sp hybridized orbitals, leading to the band-structure alteration of SrVO3 films. Mechanistic understanding of band-structure perturbation is discussed in the light of ion-solid interaction induced defect formation in SrVO3 thin films. Highlights: Fabrication of SrVO3 thin films using RF-sputtering technique. 150 KeV Cu ion implantation with ion fluence of 1.63 × 10 15 and 8.15 × 10 15 ion/cm 2 . Structural and electronic structure study using GIXRD and NEXAFS. Cu 2+ defects induced band-gap reduction of SrO3 . Cu 2+ defects altered the hybridization V 3 d and O 2p orbitals.